2013
DOI: 10.1021/jp407548a
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear THz Conductivity Dynamics in P-Type CVD-Grown Graphene

Abstract: We report strong THz-induced transparency in CVD-grown graphene where 92-96% of the peak-field is transmitted compared to 74% at lower field strength. Time-resolved THz pump/THz probe studies reveal that the absorption recovers in 2-3 ps. The induced transparency is believed to arise from nonlinear pumping of carriers in graphene which suppresses the mobility and consequently the conductivity in a spectral region where the light-matter interaction is particularly strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 33 publications
9
94
1
Order By: Relevance
“…Hwang 21 reported THz pump, THz probe measurements that showed a strong pumpinduced conductivity decrease (transmission increase) in CVD graphene samples. The THz pump can only drive intraband excitation, and should heat the carrier distribution without producing a population inversion, so this showed that population inversion is not required to observe negative differential conductivity in these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang 21 reported THz pump, THz probe measurements that showed a strong pumpinduced conductivity decrease (transmission increase) in CVD graphene samples. The THz pump can only drive intraband excitation, and should heat the carrier distribution without producing a population inversion, so this showed that population inversion is not required to observe negative differential conductivity in these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The Fermi level of graphene was determined by linear THz spectroscopy, and independently confirmed by Raman spectroscopy [3], to be at ~ 300 meV with respect to the Dirac point. In the nonlinear THz time-domain spectroscopy (THz TDS) arrangement based on tilted pulse front -pumped LiNbO 3 [4,5] (see Fig. 1), we have measured the peak-field dependent broadband conductivity of graphene in the peak THz field range 7.5 -180 kV/cm and in the spectral range 0.4 -1.6 THz.…”
Section: Measurementmentioning
confidence: 99%
“…1), we have measured the peak-field dependent broadband conductivity of graphene in the peak THz field range 7.5 -180 kV/cm and in the spectral range 0.4 -1.6 THz. We control the peak field strength in the singlecycle THz pulses using crossed wire-grid polarizers, which leaves the temporal shape of the THz waveforms unaffected [4,5]. The THz pulses were detected by free-space electro-optic sampling in a 0.5 mm thick (110)-cut ZnTe crystal.…”
Section: Measurementmentioning
confidence: 99%
“…Recent theoretical and experimental studies have demonstrated that a recorded photon absorption rate of up to 46% and a transmission modulation reaching 28% could be achieved by moderate fluences of THz pulses [18][19][20]. Furthermore, many of these results were obtained by using polycrystalline graphene fabricated by chemical vapor deposition (CVD),…”
Section: Introductionmentioning
confidence: 99%